Polarization properties of polymer-based photonic crystal fibers - Poudereux, David; Mileńko, Karolina; Dybko, Artur; Otón, José Manuel; Woliński, Tomasz R. (Photonics Letters of Poland, 2014)
Selectively filled photonic crystal fibers with polydimethylsiloxane (PDMS), a silicon-type material, have been studied. Is has been demonstrated that polarization properties of these hybrid devices and the properties of the guided light in relation with the temperature changes, finding that the state of polarization (SOP) change with the increasing temperature but remains constant for a wide spectrum of wavelengths for a determinate temperature. Full Text: PDF References T. Larsen, A. Bjarklev, D. Hermann, and J. Broeng, Optical devices based on liquid crystal photonic bandgap fibres, Opt. Express, vol. 11, no. 20, pp. 2589?2596, (2003). CrossRef H. Y. Choi, M. J. Kim, and B. H. Lee, All-fiber Mach-Zehnder type interferometers formed in photonic crystal fiber, Opt Express, vol. 15, no. 9, pp. 5711?5720, (2007). CrossRef B. Dong, J. Hao, and Z. Xu, Temperature insensitive curvature measurement with a core-offset polarization maintaining photonic crystal fiber based interferometer, Opt. Fiber Technol., vol. 17, no. 3, pp. 233?235, (2011). CrossRef D. Poudereux, P. Corredera, E. Otón, J. M. Otón, and X. Q. Arregui, Photonic liquid crystal fiber intermodal interferometer, Opt. Pura Apl., vol. 46, no. 4, pp. 321?325, (2013). CrossRef P. Lesiak, G. Rajan,Y. Semenova,G. Farrell, A. Boczkowska, A. Domanski, and T. Wolinski, A hybrid highly birefringent fiber optic sensing system for simultaneous strain and temperature measurement, Photonics Letters of Poland, vol. 2 no 3,140-142 (2010) CrossRef M. A. Unger, H.-P. Chou, T. Thorsen, A. Scherer, and S. R. Quake, Monolithic Microfabricated Valves and Pumps by Multilayer Soft Lithography, Science, vol. 288, no. 5463, pp. 113?116,(2000). CrossRef T. Thorsen, S. J. Maerkl, and S. R. Quake, Microfluidic Large-Scale Integration, Science, vol. 298, no. 5593, pp. 580?584,(2002). CrossRef K. Hosokawa and R. Maeda, A pneumatically-actuated three-way microvalve fabricated with polydimethylsiloxane using the membrane transfer technique, J. Micromechanics Microengineering, vol. 10, no. 3, p. 415, (2000). CrossRef D. C. Duffy, O. J. A. Schueller, S. T. Brittain, and G. M. Whitesides, Rapid prototyping of microfluidic switches in poly(dimethyl siloxane) and their actuation by electro-osmotic flow, J. Micromechanics Microengineering, vol. 9, no. 3, p. 211, (1999). CrossRef J. Chen, W. Wang, J. Fang, and K. Varahramyan, Variable-focusing microlens with microfluidic chip, J. Micromechanics Microengineering, vol. 14, no. 5, p. 675,(2004). CrossRef H. Lee, S.-I. Chang, and E. Yoon, A Flexible Polymer Tactile Sensor: Fabrication and Modular Expandability for Large Area Deployment, J. Microelectromechanical Syst., vol. 15, no. 6, pp. 1681?1686, (2006). CrossRef H. Kudo, T. Sawada, E. Kazawa, H. Yoshida, Y. Iwasaki, and K. Mitsubayashi, A flexible and wearable glucose sensor based on functional polymers with soft-MEMS techniques, Biosens. Bioelectron., vol. 22, no. 4, pp. 558?562, (2006). CrossRef C. Markos, K. Vlachos, and G. Kakarantzas, Guiding and birefringent properties of a hybrid PDMS/silica photonic crystal fiber, vol. 7914, pp. 791427?791427?6, (2011). CrossRef C. Kerbage and B. Eggleton, Numerical analysis and experimental design of tunable birefringence in microstructured optical fiber, Opt. Express, vol. 10, no. 5, pp. 246?255, Mar. (2002). CrossRef A. Barlow and D. N. Payne, The stress-optic effect in optical fibers, IEEE J. Quantum Electron., vol. 19, no. 5, pp. 834?839,(1983). CrossRef